Kemampuan Menganalisis Struktur Fisik dan Struktur Batin Puisi Siswa Kelas X SMA Muhammadiyah 3 Kabupaten Pulau Morotai - Sartika Samad (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to a) describe students' abilities in analyzing physical elements, namely diction, imagery, and concrete words in Chairil Anwar's poem "Doa"; and b) analyze students' abilities in analyzing spiritual elements highlighted from the aspects of theme, tone, and message in Chairil Anwar's poem "Doa". The research method used is a combination of qualitative and quantitative methods. This research was conducted at Muhammadiyah 3 High School. This research was to obtain more complete data or information with the intention that the research results were truly good. This research was conducted for two months, namely from May to July 2023. Various data collection strategies in qualitative research can generally be grouped into two types of methods, namely interactive and non-interactive data collection methods or techniques. The data analysis technique in this study systematically compiles data obtained from interviews, field notes and documentation by organizing data into categories, describing them into units, synthesizing, arranging them into patterns, choosing which ones are important and which ones will be studied, and making conclusions so that they are easily understood by oneself and others. The results of this study indicate that students at Muhammadiyah 3 Senior High School are unable to analyze the physical and inner structures of poetry due to a lack of interest in learning about literary works, particularly poetry. However, some students are able to analyze the physical and inner structures of poetry, depending on how the teacher explains the material.